Ale Rasa Beta Rasa - Ahsani Amalia Anwar; Ajuan Tuhuteru (Universitas Muslim Maros, 2020)
Pandemic Corona Virus Disease 2019 (Covid-19) has changed people’s life in various fields, including education. Face-to-face learning turns into online learning to prevent the spread of Covid-19. This article explores how the constraints faced in implementing online learning and ways which are taken to overcome them on the basis of local cultural value. This research was conducted at the Faculty of Religious Social Sciences State Institute of Christian Religion (FISK IAKN) Ambon, from which more students complaints related to obstacles encountered during online learning as compared to the two other faculties at IAKN. There were twelve people who participated in this study, consisting of two key informants (a dean and lecturer), students from various study programs, consisting of three students from Tourism, another two students from Pastoral Counseling, three students from Theology, and two from Religion and Culture study programs. Data was collected using interview via Whatsapp chatting and observation of students’ participation in online learning class, not only through Whatsapp Group, Faceboook Group, Google Classroom, Zoom, Edmodo, as well as IAKN e-learning system. The study demonstrates that in the the online learning process at FISK IAKN, students experience various problems, that include internal and external factors. Internal factors consists of limited facilities and infrastructure to support in campus online learning, students’ financial limitations, and technological illiterate of students as well as lecturers to access online learning. External factors include lack of online learning equipments, such as smartphones and laptops, unstable internet network and lack of electricity in some areas of students’ residence. Because these two factors (internal and external) are the main obstacles in the online learning process, various efforts being made to overcome them on the basis of local cultural values, ale rasa beta rasa. This is not only applied among students of FISK IAKN Ambon, but also involves parents, relatives, neighbors, lecturers, campus support and support from other institutions outside campus. The philosophy of ale rasa beta rasa has become a bonding value among fellow Ambonese and their colleagues on how they deal with problems related to the continuity of online learning in the midst of critical moment resulted from pandemic of Covid-19. The application of the social function of ale rasa beta rasa is manifested in the form of studying together; sharing information about lecture; sharing hotspots and remedial; and granting loans. Despite the fact that all constraints cannot be fully solved, there are at least somethings to be done that affect their online learning process.